Tumor-associated lymphangiogenesis in the development of conjunctival melanoma - Heindl, Ludwig M.; Hofmann-Rummelt, Carmen; Adler, Werner; Bosch, Jacobus J.; Holbach, Leonard M.; Naumann, Gottfried; Kruse, Friedrich; Cursiefen, Claus (Investigative Ophthalmology & Visual Science, 2011)
Purpose. To analyze whether tumor-associated lymphangiogenesis is concurrent with the progression of premalignant conjunctival melanocytic intraepithelial neoplasia (C-MIN) into invasive conjunctival melanoma (CM) and to study its association with prognosis. Methods. Twenty patients with CM were closely matched with 20 patients with C-MIN with atypia and 20 with C-MIN without atypia regarding tumor size, tumor location, tumor extension, and patient's age. All conjunctival specimens were analyzed for the immunohistochemical presence of proliferating lymphatic vessels, with LYVE-1 and podoplanin used as specific lymphatic endothelial markers and Ki-67 as a proliferation marker. Lymphatic vascular density was measured within the mass (intratumoral) and within an area <=500 ?m from the tumor border (peritumoral) and was correlated with recurrence, metastasis, and survival rates. Results. Intratumoral and peritumoral proliferating lymphatic vessels were detected in none of the C-MINs without atypia, in 10 of the 20 C-MINs with atypia, and in all 20 CMs. Invasive CM showed a significantly higher intra- and peritumoral density of proliferating lymphatics than did C-MIN with atypia (P <= 0.001). Patients with high intratumoral lymphatic density revealed significantly lower recurrence-free survival rates (P = 0.041) in C-MIN with atypia and significantly lower recurrence-free (P = 0.006), lymphatic-spread-free (P = 0.041), distant-metastasis-free (P = 0.029), and melanoma-specific survival rates (P = 0.029) in CM. Conclusions. Development of CM from premalignant precursors is concurrent with the outgrowth of lymphatic vessels. This active lymphangiogenesis seems to be associated with an increased risk of local recurrence in patients with C-MIN with atypia and with an increased risk of local recurrence, lymphatic spread, distant metastasis, and tumor-related death in patients with invasive CM.
EVALuna2:5320